Cognition in myotonic dystrophy type 1: a 5‐year follow‐up study. (20th June 2016) - Winblad, S.; Samuelsson, L.; Lindberg, C.; Meola, G.
Abstract : Background and purpose: Studies on cognitive decline in myotonic dystrophy type 1 (DM1) are characterized by conflicting results. The purpose of the present study was to analyse possible decline in classical/adult onset DM1 at a 5‐year follow‐up and to explore the correlation with disease‐related and demographic factors. Methods: Patients with DM1 ( n = 37) were examined with a comprehensive neuropsychological test battery yielding measures on memory, attention, verbal, visuospatial and executive functions. Assessment of muscle impairment and CTG repeat expansion size was performed. Results: A majority of the participants (65%) performed worse at follow‐up. Compared to normative data, patients scored significantly worse on tests measuring memory, attention, visuospatial construction and verbal ability. Neither CTG repeat size nor muscle impairment related to cognitive decline. However, age at onset and disease duration were correlated with the number of tests in which performance was below 1 SD at both baseline and follow‐up examination. Conclusions: Measurements show that classical/adult onset DM1 is characterized by cognitive decline. Both earlier onset and longer duration of the disease are indicative of more cognitive deficits.